Reactive neutrophil responses dependent on the receptor tyrosine kinase c-MET limit cancer immunotherapy - Glodde, Nicole Erika; Gebhardt, Christoffer (Immunity, 2017)
Inhibitors of the receptor tyrosine kinase c-MET are currently used in the clinic to target oncogenic signaling in tumor cells. We found that concomitant c-MET inhibition promoted adoptive T cell transfer and checkpoint immunotherapies in murine cancer models by increasing effector T cell infiltration in tumors. This therapeutic effect was independent of tumor cell-intrinsic c-MET dependence. Mechanistically, c-MET inhibition impaired the reactive mobilization and recruitment of neutrophils into tumors and draining lymph nodes in response to cytotoxic immunotherapies. In the absence of c-MET inhibition, neutrophils recruited to T cell-inflamed microenvironments rapidly acquired immunosuppressive properties, restraining T cell expansion and effector functions. In cancer patients, high serum levels of the c-MET ligand HGF correlated with increasing neutrophil counts and poor responses to checkpoint blockade therapies. Our findings reveal a role for the HGF/c-MET pathway in neutrophil recruitment and function and suggest that c-MET inhibitor co-treatment may improve responses to cancer immunotherapy in settings beyond c-MET-dependent tumors.
Gesehen am 08.11.2018